2016
DOI: 10.1021/acs.jpcc.6b09352
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Photoinduced Charge Separation through Donor Moiety in Donor–Acceptor Organic Semiconductors

Abstract: Three systems were designed, synthesized, and characterized to understand decay processes of photoinduced charge separation in organic semiconductors that are imperative for efficient solar energy conversion. A styrene-based indoline derivative (YD) was used as donor moiety (D), a triazine derivative (TRC) as the first acceptor (A1), and 9,10-anthraquinone (AEAQ) as a second acceptor (A2) in constructing two systems, YD-TRC and YD-TRC-AEAQ. The lifetime of the photoinduced charge-separated states in YD-TRC, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 84 publications
2
23
0
Order By: Relevance
“…A series of D-A 1 -A 2 systems were reported, with the triphenylamine (MTPA) or indoline (YD) derivative as a donor, s-triazine derivative (TRC) as the first acceptor (A 1 ), and anthraquinone derivative (AEAQ), or two perylene bisimide derivatives (PDI and PBI) as the second acceptors (A 2 ), and could be denoted as D-TRC-A 2 systems. The charge-separated states in MTPA-TRC-AEAQ system is elongated to 650 ns, more than 8 times of that in the MTPA-TRC, a simple D-A architecture (80 ns) [34,36], and the further studies suggest that charge separation efficiency and lifetime of charge-separated states may be controlled by changing the donor and second acceptor of MTPA-TRC-AEAQ [34,36,38,40]. The aforementioned ambipolar organic molecules have cascade energy levels and similar photophysical processes to generate photo-induced charge-separated states which relate to the photovoltaic performance of organic solar cells [34,37,38].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…A series of D-A 1 -A 2 systems were reported, with the triphenylamine (MTPA) or indoline (YD) derivative as a donor, s-triazine derivative (TRC) as the first acceptor (A 1 ), and anthraquinone derivative (AEAQ), or two perylene bisimide derivatives (PDI and PBI) as the second acceptors (A 2 ), and could be denoted as D-TRC-A 2 systems. The charge-separated states in MTPA-TRC-AEAQ system is elongated to 650 ns, more than 8 times of that in the MTPA-TRC, a simple D-A architecture (80 ns) [34,36], and the further studies suggest that charge separation efficiency and lifetime of charge-separated states may be controlled by changing the donor and second acceptor of MTPA-TRC-AEAQ [34,36,38,40]. The aforementioned ambipolar organic molecules have cascade energy levels and similar photophysical processes to generate photo-induced charge-separated states which relate to the photovoltaic performance of organic solar cells [34,37,38].…”
Section: Introductionmentioning
confidence: 86%
“…The charge-separated states in MTPA-TRC-AEAQ system is elongated to 650 ns, more than 8 times of that in the MTPA-TRC, a simple D-A architecture (80 ns) [34,36], and the further studies suggest that charge separation efficiency and lifetime of charge-separated states may be controlled by changing the donor and second acceptor of MTPA-TRC-AEAQ [34,36,38,40]. The aforementioned ambipolar organic molecules have cascade energy levels and similar photophysical processes to generate photo-induced charge-separated states which relate to the photovoltaic performance of organic solar cells [34,37,38]. In this work, metal-free tetraphenyl porphyrin module (HTPP) as the second electronic acceptor was firstly introduced into the MTPA-TRC system, which utilized 4,4 0 -dimethyl-4 00 -styryl-triphenylamine (MTPA) as donor and TRC as the first acceptor based on the substitution of chlorine at triazine.…”
Section: Introductionmentioning
confidence: 86%
“…Since nonconjugated chains can inhibit the back charge transfer and improve the charge separation efficiency of D-A systems, the introduction of nonconjugated chains as a bridge between the donor and the acceptor has attracted widespread attention of researchers. [37][38][39] In addition to these heterocyclic groups, between the donor and acceptor of the triphenylamine-s-triazine binary electron transfer systems nonconjugated alkyl-amino groups of different lengths were introduced. Studies showed that all the systems after the introduction of nonconjugated chains indeed show long-lived charge-separated states.…”
Section: Mtpapa-apycmentioning
confidence: 99%
“…These intramolecular processes could lead to the transient alternation of the electronic properties such as energies of electronic state, electron density distribution and dipole moments, which could tune the emission color by both covalent modifications of the fluorescence chromophores and its non‐covalent interactions with the surrounding micro‐environment . Therefore, molecules capable of ICT have practical and potential applications in sensing, nonlinear optics, catalysis, semiconducting, thermochromism, organic light‐emitting materials…”
Section: Introductionmentioning
confidence: 99%
“…[1] These intramolecular processes could lead to the transient alternation of the electronic properties such as energies of electronic state, electron density distribution and dipole moments, which could tune the emission color by both covalent modifications of the fluorescence chromophores and its non-covalent interactions with the surrounding micro-environment. [2] Therefore, molecules capable of ICT have practical and potential applications in sensing, [3,2a-c,4] nonlinear optics, [5] catalysis, [6] semiconducting, [7] thermochromism, [8] organic light-emitting materials. [9] The optical and electronic properties of perylene bisimide (PBI) dyes have been tuned by substitution, [1g,10] controlling the local π-π stacking arrangements, [11] and supramolecular assembly with electron donating/accepting molecules.…”
Section: Introductionmentioning
confidence: 99%